Survey The of Effect of Zataria multiflora Boiss. Essential Oil on the Growth of Salmonella typhimurium in a Commercial Barley Soup - MH Moosavy; AA Basti; A Misaghi; H Jabbari-Khamaneh; G Karim; T Zahraei Salehi (Institue of Medicinal Plants, ACECR, 2010)
Background: In spite of done improvements in slaughter hygiene and food production techniques, food safety is an important public health issue. Furthermore, the World Health Organization has recently called for a worldwide reduction in the consumption of salt in order to reduce the incidence of cardio-vascular disease. If the level of salt in processed foods is reduced, it is possible that other additives will be needed to maintain the safety of foods. Essential oils are probably one of the natural additives that can use as antibacterial additives. Objective: The aim of this study was evaluation of the effect of Zataria multiflora Boiss. essential oil on the growth of Salmonella typhimurium in commercial barley soup. Methods: At first, essential oil of Zataria multiflora Boiss. analyzed using GC/MS and the chemical components were identified. Antibacterial activity of Zataria multiflora Boiss. essential oil on the growth of Salmonella typhimurium in commercial barley soup evaluated by using different essential oil concentrations (0.0, 0.005, 0.015 and 0.03%) and two different temperatures(8 and 25°c) during 21 days. Results: Antibacterial activity of Zataria multiflora Boiss. essential oil on the growth of Salmonella typhimurium was statistically significant (p<0.001). The correlation coefficient of essential oil with log10 of the number of Salmonella typhimurium was -0.402. Conclusion: Zataria multiflora Boiss. essential oil probably can used as a proper preservative against some food borne pathogen bacteria in certain foods.